Impact of Shocks to Public Debt and Government Expenditure on Human Capital and Growth in Developing Countries - Kgakge-Tabengwa, Grace G. (Journal of Economics and Behavioral Studies, 2014)
This paper examines the implications of shocks to public debt and government expenditure on the development of human capital and growth within a model that explicitly recognizes the role of fiscal constraints through introducing the government budget constraint for a set of selected developing countries 1 from 1980-2013. This is mainly to capture fiscal challenges facing developing countries in developing human capital which is fundamental for sustainable growth. The dynamics of our model results reveal that high stocks of public debt, beyond the 30-40% debt/GDP threshold, depress the effect of human capital on output growth through limiting government expenditure resources available for developing human capital. Although we find that government expenditure has a positive role to play in developing human capital, sustainability becomes questionable particularly for countries where there are fiscal constraints. We conclude that developing countries which face fiscal challenges such as high public debt and poor revenue prospects to back government expenditure sustainably, cannot solely develop human capital based on the strength of their domestic resources, underscoring the need for specific supportive global fund for human capital development. The key policy implication calls for public debt management strategies and efficient government expenditure management frameworks supported by sustainable revenue prospects to provide fiscal sustenance impetus to enhance the growth process in developing countries.